2018
DOI: 10.1111/tmi.13139
|View full text |Cite
|
Sign up to set email alerts
|

The association between malnutrition and childhood disability in low‐ and middle‐ income countries: systematic review and meta‐analysis of observational studies

Abstract: Children with disabilities may be a vulnerable group for undernutrition in LMICs, which should be reflected in disability and nutritional programming and policy-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 50 publications
(83 reference statements)
0
63
0
Order By: Relevance
“…The interaction between disability and malnutrition has been reported repeatedly in different studies [5,6,7]. In their recent systematic review, Hume-Nixon et al reported a 53% positive association between childhood disability and malnutrition in LMICs [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interaction between disability and malnutrition has been reported repeatedly in different studies [5,6,7]. In their recent systematic review, Hume-Nixon et al reported a 53% positive association between childhood disability and malnutrition in LMICs [6].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between disability and malnutrition has been reported repeatedly in different studies [5,6,7]. In their recent systematic review, Hume-Nixon et al reported a 53% positive association between childhood disability and malnutrition in LMICs [6]. The review included 17 studies from LMCIs and pooled analysis showed three times higher odds of underweight and two times higher odds of stunting and wasting among children with disabilities compared to controls [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a recent systematic review of 150 studies in LMICs, 81% found that people with disabilities were economically poorer compared with people without disabilities (Banks et al 2017). Similarly, other studies have found that people with disabilities experience high levels of multidimensional poverty, such as malnutrition and lower levels of health, barriers to accessing education and healthcare, and exclusion from decent work and social participation Hume-Nixon and Kuper 2018;Mizunoya and Mitra 2013;Mizunoya et al 2018). Poverty may even be underestimated amongst people with disabilities, due for example to high out-of-pocket spending on disability-related items (e.g.…”
Section: Introductionmentioning
confidence: 99%